Kajian Kritik Sastra dengan Pendekatan Psikologi Sastra pada Cerpen Kucing Setan yang Merasakan Cinta Karya Cicilia Oday - Anggita, Dwi; Satriani, Irma (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to reveal the psychological dynamics of the main character in the short story Kucing Setan yang Merasakan Cinta by Cicilia Oday through the lens of literary psychology using Sigmund Freud's psychoanalytic theory. The short story stands out by presenting a cat character as a symbolic figure undergoing an inner transformation influenced by its social environment. Employing a qualitative descriptive method with reading and note-taking techniques as well as literature review, this research analyzes the character's personality structure based on Freud's three main components: id, ego, and superego. The results show that the cat undergoes complex psychological conflicts, where instinctual drives (id) initially dominate its behavior filled with anger and vengeance. However, as the story progresses, the development of the ego enables the character to mediate between these instinctual urges and the social norms introduced by the environment. The superego emerges as a moral compass when the character begins to experience affection and comprehend the value of sacrifice. This transformation demonstrates that even symbolic non-human characters possess psychological structures worth exploring. This study is expected to contribute to Indonesian literary criticism by expanding the analytical space for symbolic characters in short stories.